Mitochondria as the central regulator of cell death in bronchopulmonary dysplasia - Zhang, Fan; Wang, Laishuan; Zhou, Yahui (Frontiers in Physiology, 2025)
Bronchopulmonary dysplasia (BPD) remains a major chronic respiratory condition affecting preterm infants, characterized by impaired alveolar and vascular development. While the roles of oxidative stress and inflammation are recognized, this review provides a novel synthesis by positioning mitochondrial dysfunction as the central hub integrating these injurious processes with the activation of diverse cell death pathways in BPD pathogenesis. We critically explore how mitochondrial damage, driven by hyperoxia and inflammation, not only amplifies cellular injury but also orchestrates specific modes of programmed cell death, particularly apoptosis, pyroptosis, necroptosis, autophagy, ferroptosis, and the newly delineated cuproptosis. A key contribution is elucidating the crosstalk between these pathways and their collective impact on alveolar simplification and vascular dysregulation. Furthermore, we discuss the translational implications of targeting mitochondrial quality control and death pathways, proposing novel biomarkers and therapeutic strategies aimed at mitigating BPD progression. This review thus offers a unified mitochondrial-centric perspective, moving beyond descriptive mechanism to provide a conceptual framework for understanding BPD pathobiology and advancing targeted interventions.